2006
DOI: 10.1055/s-2006-947227
|View full text |Cite
|
Sign up to set email alerts
|

Boswellic Acids in Chronic Inflammatory Diseases

Abstract: Oleogum resins from Boswellia species are used in traditional medicine in India and African countries for the treatment of a variety of diseases. Animal experiments showed anti-inflammatory activity of the extract. The mechanism of this action is due to some boswellic acids. It is different from that of NSAID and is related to components of the immune system. The most evident action is the inhibition of 5-lipoxygenase. However, other factors such as cytokines (interleukins and TNF-a) and the complement system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
179
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(185 citation statements)
references
References 46 publications
3
179
0
3
Order By: Relevance
“…Pilot clinical studies indicated some therapeutic efficacy of frankincense, mainly in OA and RA (Ammon, 2006;Sengupta et al, 2008). Clinical studies using 5-LOX inhibitors (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot clinical studies indicated some therapeutic efficacy of frankincense, mainly in OA and RA (Ammon, 2006;Sengupta et al, 2008). Clinical studies using 5-LOX inhibitors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The pentacyclic triterpenes boswellic acids (BAs; Figure 1) are assumed to be the pharmacological active principles of frankincense extracts, and based on data obtained from experiments using cellular and animal models (Poeckel and Werz, 2006), there is accumulating evidence for anti-inflammatory and anti-tumorigenic effects of BAs. Pilot clinical studies have suggested some efficacy of frankincense preparations in the treatment of osteoarthritis (OA), rheumatoid arthritis (RA), inflammatory bowel diseases, asthma and cancer (see Ammon, 2006;Poeckel and Werz, 2006). Molecular mechanisms responsible for these therapeutics effects have been mainly attributed to the interference of 3-O-acetyl-11-keto-b-BA (AKBA) with signalling pathways including the nuclear factor-kB route (Syrovets et al, 2005), mitogen-activated protein kinase pathway and Ca 2+ signalling (Poeckel et al, 2006a) as well as targeting human leukocyte elastase (HLE) (Safayhi et al, 1997), 5-lipoxygenase (5-LOX) (Safayhi et al, 1992), platelet-type 12-lipoxygenase (12S-LOX) (Poeckel et al, 2006b) and COX-1 .…”
Section: Introductionmentioning
confidence: 99%
“…11 In clinical research, positive effects of boswellic acids in the treatment of inflammatory diseases could be shown. 3,12 There exist clinical trials about the use of boswellic acids in asthma, 13 rheumatoid arthritis, 14 Crohn disease, 15 collagenous colitis, 16 and osteoarthritis of the knee. 17,18 To our knowledge, there exist only first clinical observation results for the treatment of cerebral edema by boswellic acids.…”
Section: Discussionmentioning
confidence: 99%
“…The pentacyclic triterpenes (PTs) are widely distributed among plants and, due to the complex biosynthesis including cyclization of squalene, only higher plants able to carry out this catalysis contain PTs. Many plants containing PTs, in particular boswellic acids (BAs) from Boswellia serrata, have been used as anti-inflammatory remedies in folk medicine (for review see [152], [153]). …”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%
“…The most-recognized PTs that act on 5-LO are BAs, and many studies addressed the respective molecular interactions (for detailed review see [153], [156]). BAs with an 11-keto moiety, preferably 3-O-acteyl-11-keto-b-BA (AKBA 89, Table 6) are of particular interest, and AKBA 89 is the most efficient derivative with IC 50 values 1.5 ± 15 mM in intact cells [74], [154], [157], [158], [159].…”
Section: Pentacyclic Triterpenesmentioning
confidence: 99%